Pengaruh Literasi Keuangan, Self-control Keuangan, dan Gaya Hidup Terhadap Akuntabilitas Pengelolaan Keuangan pada Mahasiswa Akuntansi di Surakarta - Ayu Intan Febriana; Fadjar Harimurti (Pusat Riset dan Inovasi Nasional, 2026)
This study analyzes the determinants of financial management accountability among accounting students in Surakarta, which is triggered by the gap between academic competency and consumer behavior in the field. Using a quantitative approach and a sample of 380 students, the study examined the variables of financial literacy, self-control, and lifestyle using multiple linear regression analysis. Field findings indicate that financial literacy, self-control, and lifestyle contribute positively and significantly to improving students' financial accountability, both individually and collectively. Financial literacy was identified as the variable with the strongest influence. These findings provide implications for higher education institutions to focus not only on the cognitive aspects of finance, but also on strengthening financial character and student self-control